DEVELOPMENT AND EFFECTIVENESS OF POP-UP BOOK MEDIA INTEGRATED WITH AUGMENTED REALITY FOR SCIENCE LEARNING IN ELEMENTARY SCHOOL - Khofshotun, Dewi; Asih, Sri Sami (STKIP Citra Bakti, 2026)
This research aimed to develop, validate, and test the effectiveness of pop-up book integrated with augmented reality (AR) technology for teaching Earth structure concepts in 5th-grade students. The study employed a Research and Development (R&D) approach using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The participant group consisted of 30 fifth-grade students at SDN Bandungan 01, Kabupaten Semarang. Data collection involved validation questionnaires from subject matter experts and media experts, teacher and student response questionnaires, and pretest-posttest assessments. Results indicated that the developed media received very favorable validation ratings from subject matter experts (90%) and media experts (97%). Both teachers (100%) and students (92%) provided highly positive feedback regarding the media’s usability and attractiveness. Statistical analysis using paired sample t-tests revealed a significant difference in student learning outcomes (p = 0.000 < 0.05), with mean scores improving from 53.97 (pretest) to 79.72 (posttest), representing a moderate effect size (N-Gain = 0.55). These findings suggest that pop-up book integrated with augmented reality technology is an effective and viable instructional tool for enhancing student comprehension of complex abstract concepts in earth structure.